Amplicon Resequencing Identified Parental Mosaicism for Approximately 10% of "de novo" SCN1A Mutations in Children with Dravet Syndrome. Issue 9 (24th July 2015) - Xu, Xiaojing; Yang, Xiaoxu; Wu, Qixi; Liu, Aijie; Yang, Xiaoling; Ye, Adam Yongxin; Huang, August Yue; Li, Jiarui; Wang, Meng; Yu, Zhe; Wang, Sheng; Zhang, Zhichao; et al.
<x xml:space="preserve">Abstract</x> The majority of children with Dravet syndrome (DS) are believed to be caused by de novo SCN1A mutations. Using a new amplicon deep re‐sequencing method that we developed, we found that 8.6% (15 out of 174) of the "de novo" mutations were inherited from undetected parental mosaicism, more often from the father. Higher allelic fractions of the mosaic mutations positively correlated with mild parental epileptic symptoms. Our results highlighted the need for more sensitive detection tools in genetic counseling.